A new modelling framework to assess biogenic GHG emissions from reservoirs: The G-res tool. (September 2021) - Prairie, Yves T.; Mercier-Blais, Sara; Harrison, John A.; Soued, Cynthia; Giorgio, Paul del; Harby, Atle; Alm, Jukka; Chanudet, Vincent; Nahas, Roy
Abstract: Human-made reservoirs are now recognized as potentially significant sources of greenhouse gases, comparable to other anthropogenic sources, yet efforts to estimate these reservoir emissions have been hampered by the complexity of the underlying processes and a lack of coherent budgeting approaches. Here we present a unique modelling framework, the G-res Tool, which was explicitly designed to estimate the net C footprint of reservoirs across the globe. The framework involves the development of statistically robust empirical models describing the four major emission pathways for carbon-based greenhouse gases (GHG) from reservoirs: diffusive CO2 and CH4 emissions, bubbling CH4 emissions from the reservoir surface, and CH4 emissions due to degassing downstream the reservoir, based on an extensive meta-analysis of published data from the past three decades. These empirical models allow the prediction of reservoir-specific emissions, how they may shift over time and account for naturally occurring GHG generating pathways in aquatic networks. Graphical abstract: Image 1 Highlights: The G-res Tool is an online interface predicting the net C footprint of reservoirs. Consists of empirical models developed from an extensive meta-analysis of published data. Predicts diffusive CO2 and CH4, bubbling CH4 and degassing CH4 emissions pathways. Takes into account environmental, spatial, temporal and natural and anthropogenic effects.